Amyloid‐Based Albumin Hydrogels. Issue 7 (18th December 2022) - Diaz, Carolina; Missirlis, Dimitris
Abstract: Amyloid fibrils may serve as building blocks for the preparation of novel hydrogel materials from abundant, low‐cost, and biocompatible polypeptides. This work presents the formation of physically cross‐linked, self‐healing hydrogels based on bovine serum albumin at room temperature through a straightforward disulfide reduction step induced by tris (2‐carboxyethyl) phosphine hydrochloride. The structure and surface charge of the amyloid‐like fibrils is determined by the pH of the solution during self‐assembly, giving rise to hydrogels with distinct physicochemical properties. The hydrogel surface can be readily functionalized with the extracellular matrix protein fibronectin and supports cell adhesion, spreading, and long‐term culture. This study offers a simple, versatile, and inexpensive method to prepare amyloid‐based albumin hydrogels with potential applications in the biomedical field. Abstract : A facile and straightforward fabrication method for viscoelastic albumin hydrogels via the assembly and physical interactions of amyloid fibrils is presented. The resulting hydrogels exhibit self‐healing behavior and tunable mechanical properties and support cell adhesion and growth post‐functionalization with the extracellular matrix protein fibronectin.